2022
DOI: 10.14218/jcth.2021.00546
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Preoperative Microvascular Invasion in Hepatocellular Carcinoma Through Multidimensional Parameter Combination Modeling Based on Gd-EOB-DTPA MRI

Abstract: Background and Aims:The study established and compared the efficacy of the clinicoradiological model, radiomics model and clinicoradiological-radiomics hybrid model in predicting the microvascular invasion (MVI) of hepatocellular carcinoma (HCC) using gadolinium ethoxybenzyl diethylene triaminepentaacetic acid (Gd-EOB-DTPA) enhanced MRI. Methods: This was a study that enrolled 602 HCC patients from two institutions. Least absolute shrinkage and selection operator (Lasso) method was used to screen for the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Further studies are required to detection rate of MVI at preoperative imaging in cases with HCC. [29][30][31] The most interesting finding in our cohort was the association between cold ischemia time (CIT) and HCC recurrences. Longer CIT leads to higher cellular damage during organ retrieval and preparation, which can be directly correlated to the degree of ischemic-reperfusion injury (IRI).…”
Section: Discussionmentioning
confidence: 85%
“…Further studies are required to detection rate of MVI at preoperative imaging in cases with HCC. [29][30][31] The most interesting finding in our cohort was the association between cold ischemia time (CIT) and HCC recurrences. Longer CIT leads to higher cellular damage during organ retrieval and preparation, which can be directly correlated to the degree of ischemic-reperfusion injury (IRI).…”
Section: Discussionmentioning
confidence: 85%
“…Peritumoral HBP hypointensity indicates an impaired function of normal hepatic parenchymal cells surrounding the tumor due to the invasion of small branches of portal vein, resulting in reduced expression of organic anion transporting polypeptide and thus diminished or lost uptake of Gd-EOB-DTPA. 2 Regarding intratumor fat, the detection rate of MRI is significantly higher than that of CT, mainly because an MRI study includes multiple imaging sequences, such as chemical shift imaging, which has been recognized as the most accurate method for fat quantification. 34 A previous study has shown that intratumor fat is more common in well-differentiated HCC due to transient hypoxia in the early HCC formation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, MRI peritumoral HBP hypointensity and non‐intratumor fat were independent risk factors for discriminating MTM‐HCC. Peritumoral HBP hypointensity indicates an impaired function of normal hepatic parenchymal cells surrounding the tumor due to the invasion of small branches of portal vein, resulting in reduced expression of organic anion transporting polypeptide and thus diminished or lost uptake of Gd‐EOB‐DTPA 2 . Regarding intratumor fat, the detection rate of MRI is significantly higher than that of CT, mainly because an MRI study includes multiple imaging sequences, such as chemical shift imaging, which has been recognized as the most accurate method for fat quantification 34 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations